2017
DOI: 10.1530/rep-16-0561
|View full text |Cite
|
Sign up to set email alerts
|

Male genital tract immune response against Chlamydia trachomatis infection

Abstract: is the most commonly reported agent of sexually transmitted bacterial infections worldwide. This pathogen frequently leads to persistent, long-term, subclinical infections, which in turn may cause severe pathology in susceptible hosts. This is in part due to the strategies that uses to survive within epithelial cells and to evade the host immune response, such as subverting intracellular trafficking, interfering signaling pathways and preventing apoptosis. Innate immune receptors such as toll-like receptors ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 128 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…As chlamydial infections are the most prevalent sexually transmitted disease, as expected, the majority (n= 20) of the articles dealt with Chlamydia trachomatis or related pathogens, followed by Neisseria gonorrhoeae (n = 7), Mycoplasma spp. While most of the articles discuss the general effects of sexually transmitted male genital tract infections, only five articles [10][11][12][13][14] dealt with the long-lasting effects of the infection. Three of these articles discussed chlamydial infections [12][13][14] and two various viruses [10,11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As chlamydial infections are the most prevalent sexually transmitted disease, as expected, the majority (n= 20) of the articles dealt with Chlamydia trachomatis or related pathogens, followed by Neisseria gonorrhoeae (n = 7), Mycoplasma spp. While most of the articles discuss the general effects of sexually transmitted male genital tract infections, only five articles [10][11][12][13][14] dealt with the long-lasting effects of the infection. Three of these articles discussed chlamydial infections [12][13][14] and two various viruses [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…While most of the articles discuss the general effects of sexually transmitted male genital tract infections, only five articles [10][11][12][13][14] dealt with the long-lasting effects of the infection. Three of these articles discussed chlamydial infections [12][13][14] and two various viruses [10,11]. In the male, depending on the pathogen, the health issues reported ranged from chronic prostatitis, vesiculitis or epididymo-orchitis, leading to hormonal imbalances and testicular dysfunction, with disturbed spermatogenesis eventually resulting in temporary or permanent infertility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to trachoma, inclusion conjunctivitis, and infantile pneumonia(serovars A to C), it also causes more serious genitourinary tract infections(serovars D to K) and lymphogranuloma venereum(serovars L). The former is highly curable and can be treated with large-scale azithromycin ( 2 ), while the latter is insidious and chronic both in men and women ( 3 ). Although sensitive to antibiotics, their therapeutic benefit is limited mainly because of silent (asymptomatic) and recurrent infections attributable to immune evasion and the development of partial immunity from these infections.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, it has been demonstrated that elevated concentrations of such cytokines have been closely correlated with impaired semen parameters and, in particular – with disturbed DNA integrity. 4 5 Bacterial infections may disturb male fertility by different mechanisms. Acute infection can lead to structural defects of spermatozoa, and thus interfere with important sperm functions like motility, sperm-egg-binding, or DNA integrity, amongst others.…”
mentioning
confidence: 99%